2008
DOI: 10.1242/jcs.011262
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIIIA mobilizes transglutaminase 2 to induce chondrocyte hypertrophic differentiation

Abstract: Two transglutaminases (TGs), factor XIIIA (FXIIIA) and TG2, undergo physiologic upregulation in growth plate hypertrophic chondrocytes, and pathological upregulation in osteoarthritic cartilage. Externalization of guanine-nucleotide-bound TG2 drives chondrocyte maturation to hypertrophy, a state linked to matrix remodeling and calcification. Here, we tested the hypothesis that FXIIIA also promotes hypertrophic differentiation. Using human articular chondrocytes, we determined that extracellular FXIIIA induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 47 publications
(82 reference statements)
1
34
0
Order By: Relevance
“…Several previous studies have indicated an inductive role of ␤1 integrins in hypertrophic differentiation. Signaling via ␣1␤1 and ␣5␤1 integrins was required for hypertrophy of cultured AC chondrocytes induced by transglutaminases (33,34), ␤1 integrin-blocking antibody impaired chondrocyte hypertrophy and collagen X deposition in sternal organ culture (35), and misexpression of ␣5␤1 integrin in embryonic chick legs resulted in joint fusion and initiation of the hypertrophic differentiation program (13). Finally, we have demonstrated that hypertrophic differentiation is delayed in ␤1 fl/fl -Prx1cre ؉ mice.…”
Section: Discussionmentioning
confidence: 67%
“…Several previous studies have indicated an inductive role of ␤1 integrins in hypertrophic differentiation. Signaling via ␣1␤1 and ␣5␤1 integrins was required for hypertrophy of cultured AC chondrocytes induced by transglutaminases (33,34), ␤1 integrin-blocking antibody impaired chondrocyte hypertrophy and collagen X deposition in sternal organ culture (35), and misexpression of ␣5␤1 integrin in embryonic chick legs resulted in joint fusion and initiation of the hypertrophic differentiation program (13). Finally, we have demonstrated that hypertrophic differentiation is delayed in ␤1 fl/fl -Prx1cre ؉ mice.…”
Section: Discussionmentioning
confidence: 67%
“…FXIII-A also appears to be required intracellularly as exogenously added FXIII-A did not induce chondrocyte hypertrophy in mixed-strain (129Ola-CBACa) FXIII-A Ϫ/Ϫ chondrocytes (131). Induction of hypertrophy by FXIII-A and TG2 is associated with FAK and p38MAPK phosphorylation (131,279). These studies thus indicate important temporal signaling roles for FXIII-A and TG2.…”
Section: H Tg2 Fxiii-a Bone and Osteoarthritismentioning
confidence: 62%
“…208), all of which are in vitro TG substrates. Inhibition of chondrocyte transamidase activity reduces mineralization in preosteoblasts (18) and in cocultures of chondrocytes and preosteoblasts (209), while addition of either exogenous TG2 (132,209) or FXIII-A increases mineralization/hypertrophy (131). FXIII-A may have a more prominent role than TG2 in early matrix mineralization by intramolecular collagen cross-linking, as well as cross-linking collagen and noncollagenous matrix proteins (201).…”
Section: H Tg2 Fxiii-a Bone and Osteoarthritismentioning
confidence: 99%
“…TG2 mRNA expression in this model system also coincides with manifestations of the articular chondrocyte hypertrophic differentiation response associated with type X collagen and MMP-13 expression. Because TG2 drives both hypertrophy of cultured chondrocytes (12) and progression of articular cartilage destruction in mouse knee OA (21), TG2 appears to be a prime example of a direct modulator of chondrocyte differentiation that affects the phenotype of tissue repair in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Direct ELISA, using biotin-labeled TG2-specific antibody CUB7402 or FXIIIA specific antibody (Neomarkers, Freemont, CA) (21), was used to quantify synovial fluid levels of TG2 and FXIIIA protein (21) in studies of samples previously analyzed for COMP by ELISA (38). The fluids were concentrated with 100% TCA, and the pellet was then washed, solubilized and dissolved in buffer, and the protein was bound to a Nunc ELISA plate overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%